Alfred Adler’s Ideas and their Assimilation in Paraguay by Guillermo Enciso - García, José E. (2017)
Alfred Adler was the first dissident who left the original nucleus of psychoanalysis to establish the psychology of the individual in the mid-1910. This approach expanded gradually in many countries, including some of Latin America, where the studies of reception of the Adlerian ideas are little abundant, compared to those on the Freudian tradition. The initial comments on Adler in Paraguay date back to 1941 in an article of the Journal of Paraguayan Athenaeum, written by Guillermo Enciso, a lawyer and philosopher devoted to politics and education. Enciso used several principles of individual psychology that were consistent with their interests in social psychology and the analysis of the collective life. This article examines the assimilation of Adler’s theories by Enciso, highlighting the central concepts and comparing them with the points of view of the Paraguayan author.